Sosialisasi pemanfaatan limbah kotoran sapi menjadi biogas sebagai sumber energi alternatif di Desa Kemuning Lor, Jember - Diana Fitriati; Rizki Fitria Darmayanti; Maktum Muharja; Mohammad Nazarudin Ali; I Made Arimbawa; Filial Ahliana Rahmaniyah; Nurtsulutsiyah Nurtsulutsiyah; Hidayatullah Hidayatullah; Adelia Rosalina; Mohammad Abdul Aziz Fajar; Tri Dwinanda Nursoliha; Zakia Ainun Salsabila; Susilowati Susilowati; Achri Isnan Khamil; Rekha Aliyya Isma; Hesti Lipuring Tyas; Mohammad Nashir Idham Kholid (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Kemuning Lor Village, Jember majority working as a farmer and animal breeders especially cattle. Recorded 15 people from a total number of cattle with a total of 32 cows. One cow usually produces 10-15 kg of manure per day. According to the survey we have conducted, 5 out of 10 residents of Kemuning Lor are not aware of the use of cow dung in biogas. Volunteer activities in Kemuning Lor aim to provide education to residents in overcoming the problem of cow dung to be processed into biogas to deal with environmental pollution problems. Desa Sadar Energi program was initiated in Kemuning Lor to raise awareness from cow dung into energy that is sustainable and environmentally friendly. The implementation method consisted of pre-socialization interviews, socialization, and post-socialization interviews. There is a 72% increase in public understanding regarding the definition and use of biogas. Biogas with a digester volume of 9 m3 is equivalent to LPG of 4.14 kg. The processing of cow dung waste into biogas can reduce the cost of expenditure for household LPG so that it is more economical and the raw material, cow dung, which is abundant and sustainable, is very easy to reach by the society.